Construction of immune cell infiltration protein network based on clinical low grade glioma cases - Jiang, Wei; He, Zijian; Jiang, Weizhong; Du, Jiarui; Yuan, Lutao; Luo, Cong; Li, Xiang; Xu, Fulin (Frontiers in Oncology, 2022)
Many researchers have studied low-grade glioma and the immune microenvironment have been studied by many researchers. Recent studies suggest that macrophages and dendritic cells trigger part of the local immune dysregulation in the tumor microenvironment, and they have been polarized into a mixed pro-inflammatory and immunosuppressive phenotype. It is suggested that the degree of immune infiltration is related to the survival, therapeutic effect, and prognosis of patients. This opens up new avenues for cancer treatment. On the basis of immune infiltration degree, a protein interaction network (PIN) and a prognosis model were established, and we chose the top 20 pathways from enrichment analysis to provide potential targets for glioma clinical treatment.